Active ageing– Promotion of optimum health - Dawri, Ashalata (Indian Journal of Nursing Sciences, 2024)
The growing population, advance medical technology and increase life expectancy all over the world, at the same time pre-mature aging and increase the prevalence of chronic health problems in modern era is growing concern of health care delivery system today. Unhealthy lifestyles, faulty dietary habits, stress in life vis-à-vis decrease efficiency, energy and productivity and growing numbers of heart attacks, diabetes, hypertension and other non-communicable diseases is the global problems in developed and developing countries. Among the health care providers nurses are key resource persons in educating the population to help the community in maintains the optimum health. Find age young as long as one can keep physically and mentally fit. According to the World Health Organization (WHO), 605 million persons (20%) The life expectancy of the world population is increasing, and it is estimated that by 2025, 29% of the world population will be aged 60 years, and this will lead to an increase in the number of older people acquiring age-related chronic diseases. it is estimated that this number will have grown to 1.2 billion 29% to live these additional years independently and relatively disease and disability free will demand attention to promoting healthy lifestyles early and maintaining these throughout life. Growing old and getting sick simply are not inter-changeable. Aging may or may not be associated with disease states. Acquaint with knowledge of anti-aging, premature /signs of aging and measures to reduce its effect will beneficial to maintain wellness. In this study focused on promotion of optimum health.